2017
DOI: 10.4314/ijbcs.v11i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract candidiasis in HIV+ patients and sensitivity patterns of recovered<i> Candida </i>species to antifungal drugs in Dschang District Hospital (Cameroon)

Abstract: The incidence of Candida urinary tract infections is gradually on the rise and is an important public health problem. The aim of our study was to determine the prevalence of urinary tract candidiasis (candiduria) in HIV positive patients in Dschang District Hospital and the antifungal susceptibility test of isolates. A total of 285 patients were recruited for this study. Midstream urine samples were collected and processed using standard mycological techniques. Candida isolates were identified base on the colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
3
6
0
Order By: Relevance
“…In many studies conducted to determine the prevalence of C. glabrata cryptic species among a total of 2560 C. glabrata sensu lato isolates in eight countries or geographical locations, failed to identify either C. nivariensis or C. bracarensis, showing that these species are rare yeast pathogens in many countries or geographical locations [11]. Similar to the findings of other studies carried out in Cameroon, C. glabrata sensu stricto remains the only cryptic species of the C. glabrata complex identified from a collection of clinical isolates [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 76%
“…In many studies conducted to determine the prevalence of C. glabrata cryptic species among a total of 2560 C. glabrata sensu lato isolates in eight countries or geographical locations, failed to identify either C. nivariensis or C. bracarensis, showing that these species are rare yeast pathogens in many countries or geographical locations [11]. Similar to the findings of other studies carried out in Cameroon, C. glabrata sensu stricto remains the only cryptic species of the C. glabrata complex identified from a collection of clinical isolates [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 76%
“…Thus a prompt diagnosis of Candida infection in HIV patients and assessment of the immune status can have bearing on treatment of such infections and improve the general wellbeing of the PLWHA (people living with HIV/AIDS) [ 12 ]. The low absolute CD4+ T-lymphocyte count has traditionally been cited as the greatest risk factor for the development of oral candidiasis and current guidelines suggest increased risk once CD4+ T lymphocyte counts fall below 200 cells/μl [ 13 ]. Also, the increased incidence of mucosal and probably deep systemic forms of candidiasis has consequently made the use of antifungal agents the best option by clinicians so as to be able to control these pathogens [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have further observed a noticeable shift toward non albicans species with relative resistance to fluconazole and itraconazole [ 14 ]. The species spectrum and resistance of Candida isolates to currently available antifungal drugs is therefore a highly relevant factor because it causes important implications for morbidity and mortality [ 13 , 14 ]. During the last few decades, the spectrum of infections has undergone a drastic change; organisms with minimal or no pathogenic role have emerged as potent pathogens and organisms once susceptible have become multidrug resistant as in the case of non albicans species [ 6 , 13 -15] and Up till now, no cure exists for HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Clinical and Laboratory Standards Institute guidelines, [14] were used to prepare BaSO4 turbidity standard (0.5 McFarland's standard). Briefly, 99.5 Ml of solution A (1%v/v H2SO4) was added to 0.5 Ml of solution B (1.17% w/v BaCl2.2H2O) with constant stirring.…”
Section: Preparation Of Standardized Inoculummentioning
confidence: 99%